Australian Climate Law in Global Context / [electronic resource] - Zahar, Alexander; Peel, Jacqueline; Godden, Lee (Cambridge : Cambridge University Press, 2012)
Australian Climate Law in Global Context is a comprehensive guide to current climate change law in Australia and internationally. It includes discussion of: emission trading schemes and carbon pricing laws, laws on renewable energy, biosequestration, carbon capture and storage and energy efficiency; the trading of emission offsets between developed and developing countries, the new international scheme for the protection of forests (REDD) and the transfer of green finance and technology from developed to developing states, the adaptation to climate change through legal frameworks. It assesses the international climate change regime from a legal perspective, focusing on Australia's unique circumstances and its domestic implementation of climate-related treaties. It considers how the challenge of climate change should be integrated into broader environmental law and management. It is a valuable resource for students in law and environmental science, for current and future legal practitioners and for policy-makers and those in the commercial sector.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).